New Delhi metallo-beta-lactamase 1-producing Enterobacteriaceae: emergence and response in Europe - Struelens, M. J. (2010)
Acquired carbapenemases confer extensive antibiotic resistance to Enterobacteriaceae and represent a public health threat. A novel acquired carbapenemase, New Delhi metallo-beta-lactamase 1 (NDM-1), has recently been described in the United Kingdom and Sweden, mostly in patients who had received care on the Indian subcontinent. We conducted a survey among 29 European countries (the European Union Member States, Iceland and Norway) to gather information on the spread of NDM-1-producing Enterobacteriaceae in Europe, on public health responses and on available national guidance on detection, surveillance and control. A total of 77 cases were reported from 13 countries from 2008 to 2010. Klebsiella pneumoniae was the most frequently reported species with 54%. Among 55 cases with recorded travel history, 31 had previously travelled or been admitted to a hospital in India or Pakistan and five had been hospitalised in the Balkan region. Possible nosocomial acquisition accounted for 13 of 77 cases. National guidance on NDM-1 detection was available in 14 countries and on NDM-1 control in 11 countries. In conclusion, NDM-1 is spreading across Europe, where it is frequently linked to a history of healthcare abroad, but also to emerging nosocomial transmission. National guidance in response to the threat of carbapenemase-producing Enterobacteriaceae is available in approximately half of the surveyed European countries. Surveillance of carbapenemase- producing Enterobacteriaceae must be enhanced in Europe and effective control measures identified and implemented.